Study of the Productivity of Varietal Mulberry with Double Exploitation in the Conditions of the Syrdarya Region - N. O. Rajabov; V. K. Rahmonberdiev; G. S. Sagdullayeva (American Journal of Biology and Natural Sciences, 2024)
In the conditions of the Syrdarya region, with double exploitation, the varietal mulberry yields from 74 to 110.6 centners of leaf per hectare, i.e. almost 1.5 times more than with single exploitation. The highest yield is characterized by variety No. 5-02 (110.6 centners / ha), yielding 26.1% more than in the control Tajik seedless. Based on a three-year study of leaf formation of various combinations of mulberry with double exploitation, it can be concluded that fodder plantations on newly developed gray soils of the Syrdarya region should be laid with varietal mulberry No. 5-02.